2010
DOI: 10.1007/s00534-010-0283-3
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing acute pancreatitis caused by protein plugs in a remnant choledochal cyst

Abstract: A 49-year-old female was admitted to our hospital because of abdominal and back pains. She had undergone cystojejunostomy for a congenital choledochal cyst with pancreaticobiliary maljunction at the age of 11 years, and then underwent resection of the choledochal cyst, hepaticojejunostomy, and transduodenal sphincteroplasty at the age of 26 years. However, from 40 years of age, she had suffered from mild acute relapsing pancreatitis once every 1-2 years.On admission, the serum amylase level was elevated to 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Most authors, including those of the 2 studies noted above [7, 8] adopted endoscopic sphincterotomy, considering sphincter insufficiency [7, 8, , 15, 16]. However, other studies have reported that sphincterotomy or sphincteroplasty did not prevent the recurrence of protein plug formation after cyst excision [7, 17, 18]. Incomplete cyst excision is the cause of recurrence, because patients with recurrence always had a residual bile duct in the pancreas, and, conversely, complete excision prevented recurrence [6, 7, 17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Most authors, including those of the 2 studies noted above [7, 8] adopted endoscopic sphincterotomy, considering sphincter insufficiency [7, 8, , 15, 16]. However, other studies have reported that sphincterotomy or sphincteroplasty did not prevent the recurrence of protein plug formation after cyst excision [7, 17, 18]. Incomplete cyst excision is the cause of recurrence, because patients with recurrence always had a residual bile duct in the pancreas, and, conversely, complete excision prevented recurrence [6, 7, 17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…If the residual cyst is extremely small or if consent to remove it by surgery is not obtained, the pancreatic stone(s) should be removed by endoscopy [139]. However, as protein plugs continue to form inside the residual cyst, repeated removal of the stone(s) will be necessary.…”
Section: Commentsmentioning
confidence: 97%
“…Such a process may lead to the development of pancreatitis-like symptoms, principally involving mainly abdominal pain [139][140][141]. The treatment for such stone(s) is complete extraction of the residual cyst, because lithogenesis occurs inside the cyst.…”
Section: Commentsmentioning
confidence: 99%
“…Occasionally patients have a large remnant intrapancreatic cyst which can lead to pancreatitis secondary to protein plugs. 2 Our patient also had a remnant intrapancreatic choledochal cyst with a retained stone.…”
Section: Introductionmentioning
confidence: 60%
“…Protein stones or plugs developed in remnant IPCCs in 5% and 30% patients. 1,2 Studies have reported successful outcomes for several patients with protein stones or plugs by simply using ERCP. 3 Coexistence of an anomalous union of pancreaticobiliary duct is reported in 50%-80% cases of choledochal cysts.…”
Section: Discussionmentioning
confidence: 99%